2011
DOI: 10.1097/rhu.0b013e318205092d
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Sustained Remission of Systemic Juvenile Idiopathic Arthritis-Associated Macrophage Activation Syndrome Through Treatment With Anakinra and Corticosteroids

Abstract: We describe 2 patients with systemic juvenile idiopathic arthritis and macrophage activation syndrome. Treatment with recombinant interleukin 1 receptor antagonist (anakinra) and a corticosteroid rapidly induced remission, which could be maintained with anakinra monotherapy at a stable dose of 2 mg/kg per day. Pain at the injection site during the initial injections was the only adverse effect attributable to anakinra. Untoward effects of corticosteroid treatment were mild because prolonged therapy with high-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(77 citation statements)
references
References 9 publications
1
73
0
3
Order By: Relevance
“…An alternative therapy to etoposide is antithymocyte globulin; however, this treatment is also less commonly used in those with MAS (34). More recently, the IL-1 blocking agent, anakinra, has been successfully used to treat MAS (35); however, it should be noted that some patients with s-JIA have developed MAS while being managed with anakinra (36). Immunoglobulin (i.v.)…”
Section: Cytokinesmentioning
confidence: 99%
“…An alternative therapy to etoposide is antithymocyte globulin; however, this treatment is also less commonly used in those with MAS (34). More recently, the IL-1 blocking agent, anakinra, has been successfully used to treat MAS (35); however, it should be noted that some patients with s-JIA have developed MAS while being managed with anakinra (36). Immunoglobulin (i.v.)…”
Section: Cytokinesmentioning
confidence: 99%
“…It has been reported that infliximab, daclizumab, anakinra, vincristine, tocilizumab, and other drugs have been used in HLH salvage therapy. [9][10][11][12][13] One single-center clinical study with 38 subjects showed that initial treatment combined with antithymocyte globulins increased the complete response rate to 73%; however, the early recurrence rate was also high, and there was no superiority in long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Also anakinra, an interleukine-1 receptor antagonist, has been shown to control the inflammatory response. There are case series in which it is successfully used in the treatment of hyperinflammatory syndromes without worsening of cytopenias [12,13].…”
Section: Discussionmentioning
confidence: 99%